Follower-Characteristics as Antecedents of LMX Relationships on Organizational Performance of PWDs Institutions - Nkirote Ratanya, Scholastica (Multidisciplinary Journal of Technical University of Mombasa, 2024)
Currently, there exists great effort to ensure enhanced mainstreaming of persons living with disability (PWDs).  Such efforts have surfaced despite a myriad of challenges. This study was founded on two objectives:  follower characteristics as antecedents of LMX on organization performance in PWDs institutions and moderating effect of organization culture on follower-characteristics of LMX relationships and organization performance in PWDs institutions. The study was founded on two theories namely: Leader-Member exchange theory and Social Exchange theory. A conceptual framework presented the relationship between the variables of the study. Descriptive research design was used and the target population was lower level managers and subordinates at all levels within the organization. Stratified sampling of the various departments in the selected institutions were applied and random sampling and convenience sampling were used in the generation of the sample size. The study used a sample size of 39 and semi-structured questionnaires were used as data collection tool. A pilot study was conducted and applied Cronbach alpha reliability estimate. SPSS for windows version 21 was used to analyze data using descriptive statistics.  Study results provided a reliable follower-characteristics framework of Leader-member relationships in organizations.   One of the findings of the study was that followers possessed diverse characteristics that had a significant influence on leadership. Hence, the study concluded that focusing on follower-characteristics aids in availing new ideas on handling their work as well as interacting with their supervisors. In addition, followers are expected to ensure that they put their ego in control. The study recommends that followers are encouraged to consider fellow workers views to enhance creativity in problem solving.  The study also recommends that followers be tasked with ensuring that they hold themselves to a high standard of personal success to achieve team goals.
Keywords: Antecedents, Leader-Member Exchange(LMX), follower-characteristics